THE EFFECT OF FINANCIAL DISTRESS AND PROFIT GROWTH ON AUDIT OPINION GOING CONCERN WITH AUDIT QUALITY AS A MEDIATION VARIABLE IN MINING SECTOR COMPANIES LISTED ON THE IDX FOR THE 2017-2021 PERIOD - Sulastry Sipayung; Agus Munandar (SEAN Institute, 2023)
The purpose of this research was to examine the effect of financial distress and company profit growth on going concern audit opinion with audit quality as a mediating variable. This study used a sample of 14 mining companies listed on the IDX for the 2017-2021 period. This research uses purposive sampling technique and logistic regression analysis method to analyze the data to determine the research model and discuss the results. The results showed that financial distress had a positive effect on audit quality and on going-concern audit opinion, audit quality had a positive effect on going-concern audit opinion, while company profit growth had no significant effect on audit quality and going-concern audit opinion. This study also shows that financial distress and company profit growth simultaneously affect audit quality, financial distress and company profit growth simultaneously do not affect going-concern audit opinions, and audit quality does not mediate the effect of financial distress and company profit growth on going-concern audit opinions.